Eosinophilia and hyperglycemia: a friend or foe? - Krishna, Surabhi V. S.; Jha, Atul; Kota, Sunil K.; Bhartiya, Manish (International Journal Of Community Medicine And Public Health, 2022)
Infectious disease can precipitate new onset diabetes, complicate diabetic ketoacidosis or derange hyperglycemia. There are well studied mechanisms like an increase in production of pro inflammatory cytokine (TNF A, IL-B, and IL-6) which causes spike in the blood glucose level. However, some observational and invitro studies have shown that eosinophil do have a role in glycemic stabilization through alternatively activated macrophages (AAM). A 40-year-old male, not a known diabetic, was referred to our hospital for evaluation of high eosinophil count and hyperglycemia. He found to have severe eosinophillia, serological test for filarial positive and responded to heterazan therapy. His repeated blood smear test for microfilaria was negative. He was initially started on insulin basal bolus regimen (10 units total per day) and attained quick glycemic control with omission of insulin and with single dose of metformin 500 mg. In vitro studies on animals have also shown that when mice were fed with a diet of helminth, they showed sustained metabolic response characterized by decreased fasting glucose, improved insulin sensitivity and glucose tolerance. We discuss the controversial concept of the association whether eosinophilia increases the risk profile or does it mitigate the risk of the deadly disease, diabetes.